Consumer Insights into Dairy and Dairy Alternatives: Patterns, Perceptions, and Influencing Factors in Anand and Vidyanagar - Henil S. Patel; K.C. Kamani; M.C. Prajapati; A.K. Makwana; M.D. Gurjar (Archives of Current Research International, 2025)
This study explores consumer awareness, consumption behavior, and influencing factors related to dairy products and plant-based dairy alternatives among young adults in India. Conducted through a survey of 200 respondents, primarily students from food and agriculture disciplines, the research highlights a strong preference for traditional dairy products such as packed milk, buffalo milk, and ghee. These products are widely recognized and consumed daily, driven by convenience, nutrition, and family habits. In contrast, plant-based alternatives like almond milk, oat milk, and plant-based cheeses show low awareness, limited usage, and face barriers such as poor taste perception, unfamiliarity, and limited availability. Nutritional awareness of these alternatives is also low. The findings emphasize a significant gap between traditional and plant-based dairy products in terms of consumer acceptance. To increase adoption of plant-based alternatives, there is a need for targeted awareness campaigns, taste improvements, and better market accessibility to overcome existing perceptual and cultural barriers.